EFEKTIFITAS PEMBERIAN PROPOLIS LEBAH DAN ROYAL JELLY PADA ABSES YANG DISEBABKAN STAPHYLOCOCCUS AUREUS - NLP I Dharmayanti; E Sulistyowati; MN Tejolaksono; R Prasetya (Research Center for Biology-Indonesian Institute of Sciences, 2000)
A study was done to evaluate the effect of bee propolis and royal jelly on Staphylococcus aureus growth and duration of abscess healing.In vitro and in vivo methods were used on the study. In vitro method conducted by dilution method. In vivo 3 study treatments were divided in four groups.Each group was infected by 1.66.10 cell/ml of S.aureus fo get abscess.The group consists of treatment by abscess surgical and given bee propolis (A),abscess surgical and given royal jelly(B),abscess surgical and not given medication,and group control, no abscess surgical nor given medication.In vitro result showed minimalbactericidal concentration value of bee propolis and royal jelly were the same at concentration 6.25%.In vivo result showed duration of abscess healing were significantly different (p < 0.01).